IMPACT OF TALENT MANAGEMENT STRATEGIES ON EMPLOYEE PERFORMANCE BEHAVIOUR WITH THE MEDIATING ROLE OF TALENT MANAGEMENT OUTPUTS - al-Hussaini, Syed Hussain; Turi, Jamshid Ali; Altamimi, Abbod Naseb Abbod; Khan, Dr.Muhammad Asif; Ahmad, Mushtaq (Archives of Business Research, 2019)
The purpose of the study was to examine empirically the effect of talent management strategies on employees’ performance behavior, through mediation of talent management outputs, in telecommunication industry in Pakistan. Positivist paradigm had been used for the study. A structured questionnaire was used to collect data from a convenience sample of 200 employees of telecommunication industry located in Rawalpindi-Islamabad area. Descriptive statistics, correlation, and regression tests were used to analyze the data. The results indicated that talent management strategies significantly and positively affect employees’ performance behavior; whereas the talent management outputs partially mediate the relationship between talent management strategies and employees’ performance behavior. The results provided new insights into the phenomenon of the study. It also offered opportunities to management to plan and initiate appropriate interventions to foster employees’ performance behavior for organizations’ competitiveness.